Can saliva proteins be used to predict the onset of acute Myocardial infarction among high-risk patients? - Rahim, M.A.A.; Rahim, Z.H.A.; Ahmad, W.A.W.; Hashim, Onn Haji (2015)
Human saliva plays a pivotal role in digesting food and maintaining oral hygiene. The presence of electrolytes, mucus, glycoproteins, enzymes, antibacterial compounds, and gingival crevicular fluid in saliva ensures the optimum condition of oral cavity and general health condition. Saliva collection has been proven non-invasive, convenient, and inexpensive compared to conventional venipuncture procedure. These distinctive advantages provide a promising potential of saliva as a diagnostic fluid. Through comprehensive analysis, an array of salivary proteins and peptides may be beneficial as biomarkers in oral and systemic diseases. In this review, we discuss the utility of human salivary proteomes and tabulate the recent salivary biomarkers found in subjects with acute myocardial infarction as well as respective methods employed. In a clinical setting, since acute myocardial infarction contributes to large cases of mortality worldwide, an early intervention using these biomarkers will provide an effective solution to reduce global heart attack incidence particularly among its high-risk group of type-2 diabetes mellitus patients. The utility of salivary biomarkers will make the prediction of this cardiac event possible due to its reliability hence improve the quality of life of the patients. Current challenges in saliva collection are also addressed to improve the quality of saliva samples and produce robust biomarkers for future use in clinical applications.